Analisis Persepsi Peserta Didik Tentang Aktivitas Mengajar Guru Matematika Menggunakan Metode K-Means Clustering - Kaloka, Tesdiq Prigel; Pratomo, Danang Yugo (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2023)
Education is an important aspect of human resource development. A conducive atmosphere during the learning process is very important. This atmosphere can be assessed by students' perceptions of the teaching activities of mathematics teachers. The criteria in teaching activities are material assessment, characteristics understanding, ability to manage to learn, ability to evaluate learning, and student satisfaction. The level of student satisfaction can be determined using the results of teaching activities. In this study, we focus on determining the percentage of student satisfaction. We use K-Means Clustering to analyze the result and the Elbow Method to determine the number of clusters. For the results, we got 3 clusters with the first cluster consisting of 92 students who are quite satisfied, the second cluster with 50 satisfied students, and the third cluster having 49 students not satisfied. If we transform the result to percentage, then we have 26,18% satisfied students, 48,17% quite satisfied, and 26,65% dissatisfied.